“How should I be?” A photovoice exploration into body image messaging for young women across ethnicities and cultures - Madden, Devin; Breny, Jean M (Health Promotion Practice, 2016)
Photovoice, a community-based participatory research method that allows participants to inform research questions in an intimate way, has proven successful with youth. A diverse group of teenage girls living in New York City were asked to take photographs and reflect on what messages they received and from whom, how these messages translate across cultures and ethnicities, and how these messages are internalized and acted on. The group selected specific photographs to discuss together and themes emerged to answer the research questions; themes were reinforced by journal responses and agreed on by the group at the concluding session. The participants identified the media, peers, and family as cultural influencers on body image but noted that these messages change depending on the delivering medium. Participants not only offered recommendations with policy implications for advertising and media giants but also urged public health practitioners, teachers, and other key stakeholders working with young women of color to simply provide them with more space for talking. While Photovoice served as an effective methodology for gaining a more expansive understanding of how body image messages are received with young women of color, the tool should be considered for youth development interventions that take a community-based participatory approach. © 2015, © 2015 Society for Public Health Education.
4 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/082-186-717-498-321 tex.type: [object Object]
Keywords: *Body Image/px [Psychology]; *Ethnic Groups/px [Psychology]; *Photography; Adolescent; Body Image; Community-Based Participatory Research; Culture; Ethnic Groups; Family; Female; Humans; Mass Media; New York; New York City; Peer Group; Photography; Stereotyping; Young Adult; adolescence; adolescent; adolescent health; advertising; body image; child; child/adolescent health; health promotion; cultural anthropology; dept.pch; doctor patient relation; ethnic group; ethnicity; family; female; girl; health promotion; health research; human; human experiment; mass medium; medical research; participatory research; peer group; peer-reviewed; photography; psychology; public health; qualitative research; stereotyping; teacher; transcription regulation; women's health; women’s health; young adult

Getting men to explore safer sex responsibility: the use of Photovoice in health promotion research - Breny, Jean M.; Lombardi, Deirdre; Madden, Devin; Smoyer, Amy B. (SAGE Research Methods Cases: Health, 2017)
Keywords: dept.pch; dept.swk